Request for Clarification on catwalk and auditorium structure and spiral staircase and Vo#10 quotation for additional steel structure fabrication - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the Request for clarification on catwalk and auditorium structure and spiral staircase and Vo#10 quotation for additional steel structure fabrication of BRAC University new campus project.